PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. MONOKEM SURYA - Maha Putra; Edora Edora; Muhamad Imam Rosyidi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research was conducted at PT. Monokem Surya, located in the district. Rengasdengklok Kab. Karawang. Where the researcher wants to know whether there is an influence between reward on employee performance, the influence of motivation on employee performance and the effect of training on employee performance. The dependent variable is employee performance and the independent variables are reward, motivation and training. This research method uses quantitative methods, the data used are premier and secondary data. Primary data obtained by the questionnaire method (questionnaire). The population in this study were employees of PT. Monokem Surya as many as 70 people. The sampling technique used in this research is the total sample is saturated. The data analysis technique used in this research is validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, t test, determination test using spss software. The results showed that all independent variables had a significant effect on the performance of the employees of PT. Monokem Surya